Insights Into the Resistance Mechanisms of Inhibitors to FLT3 F691L Mutation via an Integrated Computational Approach - Sun, Yunfeng; Xia, Zhongni; Zhao, Qinqin; Zheng, Bei; Zhang, Meiling; Ying, Yin (Frontiers in Pharmacology, 2019)
Research has shown that FMS-like tyrosine kinase 3 (FLT3) may be a vital drug target for acute myeloid leukemia (AML). However, even though the clinically relevant F691L gatekeeper mutation conferred resistance to current FLT3 drug quizartinib, PLX3397 remained unaffected. In this study, the protein-ligand interactions between FLT3 kinase domain (wild-type or F691L) with quizartinib or PLX3397 were compared via an integrated computational approach. The classical molecular dynamics (MD) simulations in conjunction with dynamic cross-correlation (DCC) analysis, solvent-accessible surface area (SASA) and free energy calculations indicated that the resistant mutation may induce the conformational change of αC-helix and A-loop of the FLT3 protein. The major variations were controlled by the electrostatic interaction and SASA, which were allosterically regulated by residues Glu-661 and Asp-829. When FLT3-F691L was bound to quizartinib, a large conformational change was observed via combination of accelerated MD simulations (aMDs), principal component analysis (PCA) and free energy landscape (FEL) calculations. The umbrella sampling (US) simulations were applied to investigate the dissociation processes of the quizartinib or PLX3397 from FLT3-WT and FLT3-F691L. The calculated results suggested that PLX3397 had similar dissociation processes from both FLT3-WT and FLT3-F691L, but quizartinib dissociated more easily from FLT3-F691L than from FLT3-WT. Thus, reduced residence time was responsible for the FLT3-F691L resistance to inhibitors. These findings indicated that both the conformational changes of αC-helix and A-loop, and the drug residence time should be considered in the design of drugs so that rational decisions can be made to overcome resistance to FLT3-F691L.